Cyber-dependent crime victimization: the same risk for everyone? - Bergmann, Marie Christine (Cyberpsychology, behavior and social networking, 2018)
The Internet has simplified daily life activities. However, besides its comfortability, the Internet also presents the risk of victimization by several kinds of crimes. The present article addresses the question of which factors influence cyber-dependent crime and how they vary between three kinds of cyber-dependent offences: malware infection, ransomware infection, and misuse of personal data. According to the Routine Activity Approach, it is assumed that crime is determined by a motivated offender, the behavior of the Internet user, and the existence of prevention factors. Our analyses were based on a random sample of 26,665 Internet users in two federal states in Germany, aged 16 years and older; 16.6 percent of the respondents had experienced at least one form of cyber-dependent victimization during the year 2014. The results indicate that individual and household factors, as well as online and prevention behavior, influence the risk of cyber-dependent victimization. Furthermore, the effects differ between the three types of offences. In conclusion, the risk of being victimized by cyber-dependent crime is not the same for anyone, but depends on multivariate factors according to the idea of Routine Activity Approach. However, in view of the fact that crime-related factors also matter, studying different cybercrime offences separately seems to be an appropriate research approach.